No Detention Policy An Ontological Analysis of the Rollback Debate in India - Mishra, Preeti Vivek (JOURNAL OF INDIAN EDUCATION, 2017)
The contemporary international discourse on education and development is dominated by two perspectives, namely the human rights approach and the post-development perspective. The present article seeks to utilise the ontological-epistemological toolkit provided by these perspectives to examine the debate on rollback of No Detention Policy. The article begins with an explication of the backdrop of the rollback debate in India. It then scrutinises the arguments for and against a rollback under the respective lenses of the rights-based and post-development thought paradigms. The intent of the article is not to suggest a definite resolution to the debate but to provide an informed theoretical grounding for the stakeholders to further reason their case.